Left Distal Transradial Approach for Coronary Intervention: Insights from Early Clinical Experience and Future Directions - Hao Feng; Zhenfei Fang; Shenghua Zhou; Xinqun Hu (Cardiology Research and Practice)
Left distal transradial approach is a novel technique for coronary intervention. This technique is convenient for specialists to operate and welcomed for right-handed patients. The anatomical snuffbox and the first intermetacarpal are two available puncture sites on the basis of hand anatomy. In technical aspects, main differences between left distal transradial approach and conventional transradial approach are patient’s special position, puncture procedure, sheath choice, and hemostasis methods. According to the preliminary data, this technique is feasible and safe and it has low rate of complications including radial artery occlusion in forearm. Left distal transradial approach is a quite promising strategy of coronary intervention and deserves further exploration. In this review article, we describe the main technical characteristics and the results obtained from early clinical experiences. We also discuss the main challenges and future perspectives on this novel technique.